2021
DOI: 10.5334/gh.1071
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors and Outcomes of Contrast Induced Nephropathy in Patients with ST Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Background: Contrast induced nephropathy (CIN) is considered one of the most common causes of hospital acquired renal failure and severely affects morbidity and mortality. Our objective was to investigate incidence, predictors and outcomes of CIN in patients with ST elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI). Methods: The study was conducted on 550 patients with STEMI subjected to PPCI. Patients were classified into two groups according to the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(30 reference statements)
0
11
1
Order By: Relevance
“…So, stress hyperglycemia may aggravate the negative effects of contrast media exposure and increases the risk of contrast-induced nephropathy. Although contrast-induced nephropathy could be seen with the use of higher doses of contrast media [ 45 46 ], in the current study the volume of contrast agent showed no statistically significant difference between both groups. In agreement to our results Marenzi et al [ 47 ], who studied the effect of acute hyperglycemia and its relation to contrast-induced nephropathy in patients with STEMI after PPCI stated that, patients with acute hyperglycemia had a 2-fold higher incidence of contrast-induced nephropathy than those without acute hyperglycemia [ 34 ].…”
Section: Discussioncontrasting
confidence: 61%
“…So, stress hyperglycemia may aggravate the negative effects of contrast media exposure and increases the risk of contrast-induced nephropathy. Although contrast-induced nephropathy could be seen with the use of higher doses of contrast media [ 45 46 ], in the current study the volume of contrast agent showed no statistically significant difference between both groups. In agreement to our results Marenzi et al [ 47 ], who studied the effect of acute hyperglycemia and its relation to contrast-induced nephropathy in patients with STEMI after PPCI stated that, patients with acute hyperglycemia had a 2-fold higher incidence of contrast-induced nephropathy than those without acute hyperglycemia [ 34 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies reported that the incidence of AKI following primary PCI varied between 10%-30% defined as an increase in serum creatinine ≥ 25% or ≥ 44.2 mmol/L above baseline within 48-72 h after exposure to contrast medium. [10][11][12][13] Our study showed the incidence of AKI was about 27.0% of the whole STEMI patients, and AKI occurred as frequently with and without contrast media exposure within the first 72 h. Actually, the role of contrast media, which was the well-known predictor of AKI previously, has been questioned by Caspi, et al [14] among STEMI patients. In this study, they concluded that the rates of AKI, and risk for AKI were similar among STEMI patients regardless of exposure to contrast media.…”
Section: Discussionmentioning
confidence: 60%
“…[ 2 , 3 ] However, patients may develop contrast-induced nephropathy (CIN) after CAG or PCI, which is the third most common cause of hospital-acquired acute kidney injuries, [ 4 ] which prolongs hospital stay duration and significantly correlates with increased mortality, myocardial infarction, as well as stent thrombosis. [ 5 , 6 ] Since CIN does not have effective therapies, the early identification of patients at high risk of CIN occurrence is extremely important. A variety of risk factors for CIN have been identified, such as impaired renal function, diabetes mellitus, age, heart failure, and effective intravascular volume depletion.…”
Section: Introductionmentioning
confidence: 99%